2021
DOI: 10.4103/aian.aian_568_20
|View full text |Cite
|
Sign up to set email alerts
|

Infarct Volumes of Patients with Acute Ischemic Stroke Receiving Direct Oral Anticoagulants due to Non-Valvular Atrial Fibrillation

Abstract: Direct oral anticoagulants (DOACs) have been shown to decrease the risk of ischemic stroke in non-valvular atrial fibrillation (NVAF). This study aims to investigate whether DOACs result in a significant change in lesion volume and the severity of the subsequent disability in patients who have experienced a stroke. Methods: The study included a total of 137 patients with NVAF and acute stroke. The cohort included 76 patients using DOACs, 21 patients using acetylsalicylic acid (ASA), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Clinical evidence has shown that DOACs have a better safety profile and pharmacokinetics than warfarin in patients with NVAF 5–7 . Moreover, studies have shown that patients taking DOACs have reduced infarct volume and mRS scores compared with those taking other medications 15 . Therefore, we also evaluated whether prior anticoagulant therapy with DOACs was associated with better outcomes than warfarin therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical evidence has shown that DOACs have a better safety profile and pharmacokinetics than warfarin in patients with NVAF 5–7 . Moreover, studies have shown that patients taking DOACs have reduced infarct volume and mRS scores compared with those taking other medications 15 . Therefore, we also evaluated whether prior anticoagulant therapy with DOACs was associated with better outcomes than warfarin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The initial NIHSS score was 8 (3,15) in the prior nonanticoagulant group, 7 (2,15) in the prior insufficient anticoagulant group, and 4 (1, 7.5) in the prior adequate anticoagulant group. Similar changes in the NIHSS score and the proportion of patients with mRS ≤ 2 at discharge were observed in the 3 groups.…”
Section: Nihss On Presentation and At Discharge Mrs At Discharge And ...mentioning
confidence: 96%
See 2 more Smart Citations
“…Clot formation inhibition depends on the international normalized ratio (INR) for VKA and on plasma concentration for DOAC [ 31 ]. It is known that patients on VKA [ 32 ] or DOAC [ 33 ] therapy present with smaller infarct volumes on diffusion-weighted magnetic resonance imaging. There is some evidence showing an increased susceptibility to fibrinolysis in the presence of VKA or DOAC [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%